Determinants of Intention to Pay Professional Zakat to Private Employees: Case Study of Muzakki Laznas Daarut Tauhiid Peduli - Sadili, Ujang; Ali, Zulkarnain Muhammad; Zaenal, M. Hasbi (Penerbit Goodwood, 2024)
Purpose: This study aims to identify and analyze the factors which affect the intention to pay zakat on private employees Methodology: This qualitative research used SEM-PLS with primary data collected from questionnaires based on convenience sampling, totaling 100 respondents. Results: Religious figures and peers influenced the subjective norms of private employees' intention to pay for zakat. Perceptions of behavioral control on employees’ intention to pay zakat are influenced by zakat knowledge, zakat law enforcement, and the quality of zakat distribution. Attitudes, subjective norms and perceptions of behavioral control directly influence employees' intentions to pay professional zakat Limitations: The targets used in the research were LAZNAS DT Peduli donors, private employees and ASN employees/entrepreneurs who had zakat income as a comparison.The targets used in the research were LAZNAS DT Peduli donors, private employees and ASN employees/entrepreneurs who had zakat income as a comparison. Contribution: The results of the research show that the dominant factor influencing the perception of the behavioral control variable is the knowledge that the distribution of zakat funds carried out by private employees of LAZNAS DT Peduli is expected to be able to change mustahiq into muzakki. The practical implication of this research is that religious figures such as K.H. are important in distributing zakat. Abdullah Gymnastiar is influential in this matter in inviting and influencing private employees to give zakat to LAZNAS DT Peduli and the DT Peduli zakat institution is one of the institutions that distributes professional zakat that muzakki are interested.